PARTISIPASI ORANG TUA DALAM MENINGKATKAN POLA ASUH ANAK USIA DINI MELALUI KEGIATAN PARENTING DI PAUD MELATI PUTIH KECAMATAN UJUNGBERUNG (Studi Deskriptif di PAUD Melati Putih Kecamatan Ujungberung) - Susilowati, Rini; Permana, Omo; Handayani, Heni (Pimpinan Cabang Muhammadiyah Kramat Jati, 2022)
The background of this research is because there are still many parents who are wrong in applying parenting to their children, this is due to various things including the busyness of parents who have various activities and also parents who do not understand the form of parenting applied to their children. Parents should participate in the implementation and monitoring and evaluation of parenting. Therefore, the objectives of this study are to: 1) Knowing the role of parents in improving the child's upbringing. 2) Knowing the form of parenting style for their children. 3) Knowing the factors that support the participation of parents and schools. This study used a qualitative approach with descriptive methods, the subjects studied consisted of: managers, teachers, and parents, with data collection tools using observation, interviews and documentation techniques. The results showed that: 1) The forms of participation contained in the school program were parenting, communication, and learning at home. Parents act as supporters, 2) The form of parenting in the family, proper parenting is a form of parenting from both parents and teachers given to children who have the freedom and rules to adapt to the conditions of each child. 3) Supporting and inhibiting factors for successful parenting can limit the success of the program. Supporting factors include aspects of age, gender, education, and occupation. While the inhibiting factors such as the attitude of the teacher, the teacher's view of parents and the lack of information